An Analysis of the Factors Affecting Public Participation in Environmental Impact Assessment: Case Study of Selected Projects in Nairobi City County, Kenya - Atieno, Onyango Leah; Mutui, Frida Nyiva; Wabwire, Evans (European Scientific Journal, ESJ, 2019)
Public Participation (PP) is an integral part in the EIA process and it is enshrined in the Constitution of Kenya. The overall objective of the study is to evaluate the factorsthat affect public participation in EIA process among selected projects in Nairobi City County. The specific objectives of the study were to evaluate how socio- economic, behavioral and political factors affect PP in EIA process. Two theories that were used in this study included OECD active participation framework and CLEAR participation model. The study adopted descriptive research design. The researcher targeted five projects from 53 on- going projects in Nairobi County. The population of the study included 105 respondents (100 participants and 5 project proponents). That is 20 respondents from each project. The researcher used questionnaires (participants) and interviews guides (project proponents) to collect data. Data collected was both quantitative and qualitative. The findings revealed that the level of education affects public participation in projects. Language used during meetings could either encourage/ discourage effective communication hence have an effect on participation. Employment status tend to affect how public participate in EIA process. The level of trust between the government and public tends to affect how the public will come out to participate in government projects when called upon. Politicians had an influence on public participation in government projects. The study recommends regularly awareness by National Environment Management Authority about EIA process and the public should change their attitude towards participation in government projects.